A comparative investigation on the physio-chemical properties and some selected enzymes content in the flesh of healthy and Rhizopus stolonifer infected moringa fruit - and NURUL ABSAR, M. ZOADUR RAHMAN*, ZAHANGIR ALAM SAUD (Indian Phytopathology, 2002)
The physio-chemical composition of healthy and diseased moringa fruits were investigated at different maturity levels. Of varieties examined, Najna contained highest amount of protein, total sugar, reducing sugar, total soluble solid (TSS), starch and ash while Sajina contained highest amount of total titrable acidity (TTA), moisture, lipid, vitamin C. In both the healthy and diseased conditions, total sugar, reducing sugar, sucrose, TSS, moisture, protein and lipid content were increased but ash, total titrable acidity (TTA) and vitamin C content decreased moderately with the changes of maturity. Starch content changes very rapidly after mature stage. All the nutrient contents under investigation except protein, reducing sugar and ash were decreased after infection of moringa fruits with disease. The activities of all the seven enzymes under investigation were increased after infection of moringa fruits. The activities of catalase and protease increased but that of polyphenol oxidase and ascorbic acid oxidase decreased remarkably with the advancement of maturity stages and the activities of amylase, cellulase and invertase increased upto mature stage and then decreased abruptly.